Familial craniosynostosis, anal anomalies, and porokeratosis: CAP syndrome. Issue 9 (September 1998) - Flanagan, N; Boyadjiev, S A; Harper, J; Kyne, L; Earley, M; Watson, R; Jabs, E W; Geraghty, M T
Abstract : We report on the occurrence of coronal craniosynostosis, anal anomalies, and porokeratosis in two male sibs. A third male sib was phenotypically normal as were the parents. The occurrence of these three clinical features has, to our knowledge, not been reported before. Cutaneous or anal anomalies or both have been reported in a number of syndromes associated with craniosynostosis, including Crouzon, Pfeiffer, Apert, and Beare-Stevenson syndromes. These syndromes are associated with mutations in the fibroblast growth factor receptor genes FGFR1, FGFR2, and FGFR3. They are inherited in an autosomal dominant fashion. In contrast, the cases we report do not carry any of the common FGFR mutations and the pedigree suggests autosomal or X linked recessive inheritance.